Preferred iconography for development of new garden identity - Kaboudarahangi, Mina (2012)
Globalization is fast transforming our world into one featureless place, leaving most nations with a lacking sense of identity. Some of the key areas affected by globalization include landscapes and gardens. Generally considered as symbols of national identity, the establishment of a nationally defined garden can contribute greatly to the development of a distinct national identity. Well-established gardens throughout history have proven to boast a nation’s identity through time, philosophy, tradition, and the cultural background of its people. These historical gardens are easily recognized through particular images that illustrate their distinctive iconographies. However, the iconography of new developing gardens is still unclear. If these new gardens do not reflect the specific cultures or values and needs of its users, then a unique set of problems will arise, particularly a low level of appreciation and acceptance. Exploring garden iconographies, this study surveyed related garden preferences and has made suggestions for the development of a new garden identity. Malaysia — a fast developing country with great potential for and an interest in garden development — was selected as a case study. In accordance with this subject, photo preference surveys explored the preferred iconography for new Malaysian gardens and determined the factors affecting these preferences. Meanwhile, face-to-face interviews with Iranian and Malaysian landscape experts clarified the issues and challenges pertaining to garden development. It is important to note that the findings of this study can be used to contribute to the formation of Malaysian gardens with a distinct Malaysian identity. It can also be extended or adopted by other nations hoping to achieve or enhance national identity through garden development.